A strong wet-adhesion material, its preparation method and application

CN116284849BActive Publication Date: 2026-10-30TONGJI UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202211100634.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-08
Publication Date
2026-10-30
Estimated Expiration
2042-09-08

AI Technical Summary

Technical Problem

如果不及时进行适当的维修,会影响隧道运营,甚至对经济和社会造成重大损害

Benefits of technology

1. 本发明的湿粘附材料,在制备时采用容易获取且成本低的原材料,该强湿粘附材料为双层水凝胶,使用方法简单,如同胶带一般直接贴在混凝土缺陷表面即可,且不论是在有水环境中还是渗水环境中均可使用,与传统的涂层、灌浆法相比,无需采取封闭排水措施、施工窗口期段,使用限制因素更少。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116284849B_ABST
    Figure CN116284849B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of strong wet adhesion material and its preparation method and application, the strong wet adhesion material is double-layer hydrogel, the double-layer hydrogel includes tough layer hydrogel and adhesive layer hydrogel, the component of the adhesive layer hydrogel penetrates into the network of the tough layer hydrogel, and there is interlocking structure at junction.The preparation method is as follows: with acrylamide, 2-phenoxy ethyl acrylate, dimethyl sulfoxide, first crosslinking agent and first initiator as raw material to obtain tough layer hydrogel, with dopamine, water, clay nanosheet, acrylamide, second crosslinking agent and second initiator as raw material, obtain reaction solution and pour it to the upper surface of the tough hydrogel, obtain adhesive layer hydrogel, to obtain double-layer hydrogel, i.e strong wet adhesion material.Compared with prior art, the present application can realize concrete leakage effective, fast, convenient repair, provide necessary dry condition for other repair means, thereby prolong the service life of structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of underwater suspended tunnel technology, and in particular to a strong wet adhesion material, its preparation method and application. Background Technology

[0002] Submerged Floating Tunnels (SFTs) are a new type of transportation structure that spans straits, bays, lakes, and other waterways. This novel structure effectively utilizes the buoyancy of water, hence its alternative name, the Archimedes' Bridge. SFTs significantly shorten travel distances and improve transportation efficiency. They are virtually unaffected by weather, environment, terrain, or natural disasters, and offer economic and technological advantages for long spans. As a novel sea-crossing solution that balances accessibility and environmental considerations, SFTs provide a new and effective way to establish convenient transportation networks in waterways where traditional methods are difficult.

[0003] The tubes of underwater suspended tunnels are generally made of reinforced concrete. Similar to traditional concrete, they are inevitably susceptible to damage and even performance degradation due to initial defects, material aging, corrosive media, continuous traffic loads, and natural disasters. Especially underwater, the tubes are constantly subjected to loads from water flow and waves, as well as seepage erosion. They may also be impacted by aquatic organisms, boats, and fishing equipment, leading to cracking, delamination, deformation, spalling, leakage, and steel corrosion. Among these, leakage due to cracks is the most common type of tunnel-related problem. If not repaired promptly and appropriately, it can affect tunnel operation and even cause significant economic and social damage.

[0004] For the repair of leaks and cracks in buildings, existing methods mainly include epoxy resin repair and re-pouring after removing deteriorated materials. These methods generally require prior waterproofing treatment, such as sealing cracks or joints, coating repair, grouting, and water diversion. However, these methods have many limitations and are complex to implement, especially in the presence of water, where the adhesion between the repair material and the concrete substrate is severely weakened, significantly limiting their application and making timely repair difficult. For example, the invention patent CN102775737A, "A Solvent-Free Elastic Epoxy Grouting Material and Its Preparation Method and Application," discloses a solvent-free elastic epoxy grouting material comprising epoxy resin, reactive diluent, curing agent, accelerator, and dispersant. While this material is environmentally friendly, has good groutability, and a suitable working time, its long working time means that during crack repair, the grout may leak out of the crack under pressure and gravity before curing, preventing it from filling the crack and affecting the material's sealing effect. Summary of the Invention

[0005] The purpose of this invention is to overcome the defects of the prior art by providing a strong wet adhesion material, its preparation method and application, to achieve effective, rapid and convenient repair of concrete leakage, and to provide the necessary drying conditions for other repair methods, thereby extending the service life of the structure.

[0006] The objective of this invention can be achieved through the following technical solutions: The first objective of this invention is to provide a method for preparing a strong wet adhesion material, comprising the following steps: 1) Acrylamide (AM), ethyl 2-phenoxyacrylate (PEA), dimethyl sulfoxide (DMSO), the first crosslinking agent and the first initiator are added to the reaction mold, stirred evenly, sonicated, and heated to obtain PAM-PEA hydrogel, i.e. tough layer hydrogel; 2) Prepare a clay-polydopamine (PDA) suspension by mixing dopamine (DA), water, and clay nanosheets. Add acrylamide (AM), a second crosslinking agent, and a second initiator to the clay-polydopamine (PDA) suspension, stir evenly, and sonicate to obtain a reaction solution. Pour the obtained reaction solution onto the upper surface of the tough hydrogel obtained in step 1), and heat it to synthesize a PDA-clay-PAM hydrogel, which is the adhesion layer hydrogel, thus obtaining a double-layer hydrogel, which is the strong wet adhesion material.

[0007] Preferably, the first crosslinking agent in step 1) is N,N'-methylenebisacrylamide (MBAA).

[0008] Preferably, the first initiator in step 1) is potassium persulfate (KPS).

[0009] Preferably, the total concentration of acrylamide (AM) and ethyl 2-phenoxyacrylate (PEA) in step 1) is 2-5 mol / L, wherein the molar ratio of ethyl 2-phenoxyacrylate (PEA) is 70-90%.

[0010] Preferably, the concentration of the first crosslinking agent in step 1) is 1×10⁻⁶. -4 -2.5×10 -4 mol / L; Preferably, the concentration of the first initiator in step 1) is 0.2 × 10⁻⁶. -3 -0.8×10 -3 mol / L.

[0011] More preferably, the concentration of the first initiator is 0.5 × 10⁻⁶. -3 .

[0012] Further, the stirring rate in step 1) is 300 rpm, and the time is 5-15 min.

[0013] More preferably, the stirring rate in step 1) is 300 rpm and the time is 10 min.

[0014] Furthermore, the ultrasound power in step 1) is 200 W, and the duration is 10-20 min; More preferably, the ultrasound time in step 1) is 15 minutes.

[0015] Further, the heating in step 1) is water bath heating, the heating temperature is 55-65℃, and the time is 20-40 min.

[0016] More preferably, the temperature of the water bath in step 1) is 60°C and the time is 30 min.

[0017] Preferably, the water in step 2) is deionized water.

[0018] Preferably, in step 2), the second crosslinking agent is N,N'-methylenebisacrylamide (MBAA).

[0019] Preferably, the second initiator in step 2) is potassium persulfate (KPS).

[0020] Preferably, the concentration of acrylamide (AM) in step 2) is 2-5 mol / L; Preferably, in step 2), the mass ratio of dopamine (DA) to acrylamide (AM) is DA:AM = x wt%, where 0 < x ≤ 8.

[0021] Preferably, in step 2), the mass ratio of clay nanosheets (Clay) to acrylamide (AM) is Clay:AM = 4-12 wt%.

[0022] Preferably, the concentration of the second crosslinking agent in step 2) is 1×10⁻⁶. -4 -2.5×10 -4 mol / L; Preferably, the concentration of the second initiator in step 2) is 0.2 × 10⁻⁶. -3 -0.8×10 -3 mol / L.

[0023] More preferably, the concentration of the second initiator is 0.5 × 10⁻⁶. -3 mol / L.

[0024] Further, the stirring rate in step 2) is 550 rpm, and the time is 20-30 min.

[0025] More preferably, the stirring rate in step 2) is 550 rpm and the time is 25 min.

[0026] Furthermore, the ultrasound power in step 2) is 200 W, and the duration is 20-40 min.

[0027] More preferably, the ultrasound time in step 2) is 30 min.

[0028] Furthermore, the heating described in step 2) is water bath heating, and the heating temperature is 75-85℃ for 50-70 min.

[0029] More preferably, the heating temperature in step 2) is 80°C and the heating time is 60 min.

[0030] Furthermore, the preparation of the clay-polydopamine suspension in step 2) specifically includes the following steps: Dopamine (DA) was dissolved in water to obtain an aqueous DA solution; clay nanosheets were added to the obtained aqueous DA solution to prepare a clay-DA suspension; the obtained clay-DA suspension was stirred at 550 rpm for 5 h to obtain a clay-polydopamine suspension.

[0031] The second objective of this invention is to provide a strong wet adhesion material prepared by the above-described preparation method. This strong wet adhesion material is a bilayer hydrogel, comprising a toughening layer hydrogel and an adhesion layer hydrogel. The components of the adhesion layer hydrogel permeate into the network of the toughening layer hydrogel, and an interlocking structure exists at the junction. The toughening layer hydrogel is a PAM-PEA hydrogel, and the adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

[0032] A third objective of this invention is to provide an application of the aforementioned strong wet adhesion material for the rapid repair of cracks in underwater suspended tunnels.

[0033] Furthermore, the adhesive material is adhered to the surface of a cracked concrete specimen, which is then immersed in water with an aqueous solution pH varying from 6.0 to 9.0.

[0034] Furthermore, the application process includes the following steps: S1) Prepare a tubular concrete specimen model with cracks to simulate the morphology of an underwater suspended tunnel; S2) Fix the lower end of the concrete tubular specimen to the bottom of the water tank with epoxy resin, fill the water tank with water to a level higher than the crack, so that the crack becomes the only water inlet point, cut the prepared strong wet adhesion material into appropriate sizes and stick it to the crack, and the pH of the aqueous solution is 6.0-9.0 to simulate different water quality environments.

[0035] More preferably, the tubular concrete specimen model has a specimen thickness of 4 cm, a height of 50 cm, an outer diameter of 30 cm, and a crack width of 0.2 mm.

[0036] This invention innovatively utilizes the toughness, responsiveness, self-healing, and adhesion of intelligent hydrogels, employing polymer hydrogels as a strong wet adhesive for the rapid repair of underwater suspended tunnels. Hydrogels are multi-component systems composed of a three-dimensional cross-linked polymer network and water. The hydrophilic groups in the three-dimensional network can bind extensively with water, causing the hydrogel to swell. The presence of the cross-linked network hinders the hydrogel's dissolution in water, thus maintaining its macroscopic structural integrity. This endows the hydrogel with the unique property of being hydrophilic but insoluble in water. Through rational composition and structural design of the polymer network of the hydrogel, and the introduction of chemical or physical cross-linking, excellent wet adhesion and mechanical properties can be acquired, achieving strong adhesion in aquatic environments. This provides the possibility for its use as a wet-adhesive repair material. Furthermore, because hydrogels are materials with a three-dimensional network structure and inherently possess "soft-wet" properties and good compatibility, they can be well adapted to concrete systems. Based on the wet adhesion mechanism of hydrogels and the application condition of concrete substrates in a wet environment, this invention has identified suitable raw material composition and proportions, as well as a preparation process. It has successfully utilized acrylamide, ethyl 2-phenoxyacrylate, dopamine, and clay nanosheets as raw materials, and found suitable reaction temperatures and processing methods to produce a strong wet adhesive with wet adhesion properties. This adhesive can remove interfacial moisture and adhere strongly to the concrete surface in a wet environment. Specifically, using acrylamide and ethyl 2-phenoxyacrylate, and acrylamide, dopamine, and clay nanosheets as reaction systems respectively, a two-step "superposition" method was used to prepare a tough, highly resilient hydrogel layer and a strong interfacial adhesion hydrogel layer. Because the components of the adhesion layer can penetrate into the network of the tough layer, an interlocking structure is generated at the bonding point during the manufacturing process, thus the two hydrogel layers are almost seamlessly connected. The toughening layer is rich in aromatic hydrophobic 2-phenoxyacrylate groups, which, through hydrophobic copolymerization and π-π interactions, endow the polymer network with superior energy dissipation capabilities, enhancing the cohesive strength of the gel. Dopamine contains catechol groups, therefore the dopamine-based adhesive layer hydrogel is rich in catechol groups. These groups can penetrate the hydration layer and form interfacial interactions with underwater substrates through hydrogen bonding, metal coordination, and π-π / cation-π interactions. Furthermore, these groups undergo covalent cross-linking under oxidative conditions, giving the catechol-based hydrogel excellent adhesion properties on almost all water-immersed matrices. These two hydrogel layers are organically combined, each with different functions, complementing each other. This bilayer hydrogel can be used as a strong wet-adhesive material for the rapid repair of underwater suspended concrete tunnels, improving the concrete structure's ability to resist water erosion in wet environments.

[0037] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. The wet adhesion material of the present invention is prepared using readily available and low-cost raw materials. This strong wet adhesion material is a double-layer hydrogel. It is easy to use, and can be directly applied to the surface of concrete defects like tape. It can be used in both wet and seeping environments. Compared with traditional coating and grouting methods, it does not require sealing and drainage measures or construction window periods, and has fewer limiting factors.

[0038] 2. The strong wet adhesion material of the present invention is prepared by free radical polymerization in a two-step process. Experiments show that the equilibrium swelling rate of the bilayer hydrogel is as low as 12.37%, and the wet adhesion strength can reach as high as 136.5 kPa. This wet adhesion material can effectively and timely repair concrete cracks.

[0039] 3. The strong wet adhesion material of the present invention can easily and effectively repair defects such as concrete cracks in complex water environments, effectively block the intrusion of external moisture and corrosive ions into the concrete interior, and extend the service life of underwater suspended tunnel concrete. Attached Figure Description

[0040] Figure 1 This is a schematic diagram of the tough-adhesive double-layer structure of the strong wet adhesion material provided by the present invention.

[0041] Figure 2 This is a schematic diagram illustrating the application process of the strong wet adhesion material provided by the present invention.

[0042] Figure 3 This is a schematic diagram of the wet adhesion strength test of the strong wet adhesion material provided by the present invention.

[0043] Figure 4 The equilibrium swelling rate curve of the strong wet adhesion material provided by the present invention.

[0044] Figure 5 The diagram shows the wet adhesion strength and adhesion energy of the strong wet adhesion material provided by the present invention. Detailed Implementation

[0045] The present invention will now be described in detail with reference to the accompanying drawings and specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but do not limit the invention in any way. It should be noted that those skilled in the art can make several modifications and improvements without departing from the concept of the present invention. These all fall within the protection scope of the present invention.

[0046] Any preparation methods, materials, structures, or composition ratios not explicitly described in this technical solution are considered common technical features disclosed in the prior art.

[0047] In this invention, clay nanosheets, (Na)0.33 (Mg 2.66 Li 0.33 Si4O 10 (F,OH)2.

[0048] In this invention, the raw materials used to prepare ordinary concrete are: PO 42.5 ordinary Portland cement; natural river sand, specifically medium sand with a fineness modulus of 2.7, meeting the requirements of the standard specification "Sand for Construction" (GB / T14684-2011); and 5-40mm graded gravel, meeting the requirements of the standard specification "Gravel and Crushed Stone for Construction" (GB / T14685-2011). Pure tap water is used directly for mixing, meeting the requirements of the standard specification "Standard for Water Used in Concrete Mixing" (JGJ63-2006). The mix design follows the "Specification for Mix Design of Ordinary Concrete" (JGJ55-2011), and the design strength grade of the concrete is C40. The concrete mix proportions are shown in Table 1.

[0049] Table 1 Concrete mix proportions. Comparative Example This comparative example provides a method for preparing a strong wet adhesion material, including the following steps: 1) Acrylamide (AM), ethyl 2-phenoxyacrylate (PEA), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) are added to a dimethyl sulfoxide (DMSO) solution in a reaction mold. The total concentration of acrylamide (AM) and ethyl 2-phenoxyacrylate (PEA) is 4 mol / L, the concentration of ethyl 2-phenoxyacrylate (PEA) is 80% of the total concentration, and the concentration of N,N'-methylenebisacrylamide (MBAA) is 2 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 The solution was stirred evenly with a magnetic stirrer, then degassed by ultrasound, and then reacted by water bath heating to obtain PAM-PEA hydrogel, i.e., tough layer hydrogel. The stirring rate was 300 rpm, the stirring time was 10 min, the ultrasound power was 200 W, the ultrasound time was 15 min, the water bath heating temperature was 60℃, and the water bath heating time was 0.5 h.

[0050] 2) Dopamine (DA) was dissolved in deionized water, and clay nanosheets (Clay) were added. The mixture was stirred for 5 hours at a stirring rate of 550 rpm to allow dopamine intercalation and oxidation, preparing a clay-polydopamine (clay-PDA) suspension. Acrylamide (AM), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were then added to this clay-polydopamine suspension to obtain a reaction solution. The concentration of acrylamide (AM) was 4 mol / L, the mass ratio of dopamine (DA) to acrylamide (AM) was DA : AM = 0 wt% (A0), the mass ratio of clay nanosheets (Clay) to acrylamide (AM) was Clay : AM = 10 wt%, and the concentration of N,N'-methylenebisacrylamide (MBAA) was 2 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. - 3 After stirring evenly with mol / L, the solution was degassed by ultrasound. The reaction solution was then poured onto the upper surface of the tough hydrogel obtained in step 1). PDA-clay-PAM hydrogel, i.e., the adhesion layer hydrogel, was prepared by water bath heating, thus obtaining a double-layer hydrogel. This double-layer hydrogel is a strong wet adhesion material. The stirring rate was 550 rpm, the stirring time was 25 min, the ultrasound power was 200 W, the ultrasound time was 30 min, the water bath heating temperature was 80℃, and the water bath heating time was 1 h.

[0051] Figure 1 This is a schematic diagram of the tough-adhesive bilayer structure of the strong wet adhesion material provided by the present invention, as shown below. Figure 1 As shown, the strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel; the components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction; the tough layer hydrogel is PAM-PEA hydrogel; the adhesion layer hydrogel is PDA-clay-PAM hydrogel.

[0052] The aforementioned strong moisture-adhesive material was applied to the rapid repair of cracks in underwater suspended tunnels. Specifically, the material was directly adhered to the surface of a cracked concrete specimen immersed in water, as illustrated in the diagram. Figure 2 As shown. The application process includes the following steps: S1) Prepare a tubular concrete specimen model with cracks to simulate the shape of an underwater suspended tunnel. The specimen is 4 cm thick, 50 cm high, 30 cm in outer diameter, and the crack width is 0.2 mm. S2) Fix the lower end of the tubular concrete specimen model to the bottom of the water tank with epoxy resin, fill the water tank with water to a level higher than the crack, so that the crack becomes the only water inlet point, cut the prepared strong wet adhesion material to the corresponding size, and stick it to the crack. The pH of the aqueous solution is 8.0 to simulate the most common weakly alkaline water environment.

[0053] The swelling rate and wet adhesion strength of the strong wet adhesion material in this comparative example were tested.

[0054] The swelling rate test method is as follows: Separate the solidified hydrogel from the mold and immerse it in deionized water. Change the water every 12 hours until swelling equilibrium is reached. Measure the mass at regular intervals (remove surface water with filter paper) until the difference between two mass measurements does not exceed 0.01g.

[0055] Swelling ratio SR = (M t -M i ) / M i Among them, M t The mass after swelling for a period of time, M i The mass at the initial synthesis. The swelling rate after reaching swelling equilibrium is the equilibrium swelling rate.

[0056] The wet adhesion strength test method is as follows: A schematic diagram of the wet adhesion strength test is shown below. Figure 3 As shown, the test was conducted on a universal testing machine. The hydrogel had a diameter of 15 mm and a thickness of approximately 10 mm. First, cyanoacrylate (a strong adhesive) was used to adhere the gel to the probe of the universal testing machine. Then, the gel (on the probe) was immersed in the solution containing the test specimen for 5 minutes to allow it to equilibrate before the test. The probe approached the substrate surface at a speed of 10 μm / s, held under applied pressure for 10 s, and then retracted at a speed of 100 μm / s. To ensure sufficient contact between the adhered hydrogel and the substrate, a pressure equal to the elastic modulus of the specimen was applied in the wet adhesion strength test. All tests were conducted in water at room temperature. The wet adhesion strength was determined by dividing the maximum adhesion force by the adhesion strength, and the adhesion energy was calculated based on the ratio of the integral area under the load-displacement curve of the adhesion test to the adhesion area. The test results are as follows: Figure 4 , Figure 5 As shown in the figure, the test results of this comparative example correspond to A0 in the figure.

[0057] Example 1 This embodiment provides a method for preparing a strong wet adhesion material. In this embodiment, the mass ratio of dopamine (DA) to acrylamide (AM) in step 2) is DA : AM = 2 wt% (A2).

[0058] The remaining steps are the same as in the comparative example.

[0059] The strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel. The components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction. The tough layer hydrogel is a PAM-PEA hydrogel. The adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

[0060] The above-mentioned strong wet adhesion material was applied to the rapid repair of cracks in underwater suspended tunnels. The specific method and application process are the same as those in the comparative example.

[0061] The swelling rate and wet adhesion strength of the strong wet adhesion material in this embodiment were tested.

[0062] Test results are as follows Figure 4 , Figure 5 As shown in the figure, the test results of this embodiment correspond to A2 in the figure.

[0063] Example 2 This embodiment provides a method for preparing a strong wet adhesion material. In this embodiment, the mass ratio of dopamine (DA) to acrylamide (AM) in step 2) is DA : AM = 4 wt% (A4).

[0064] The remaining steps are the same as in the comparative example.

[0065] The strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel. The components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction. The tough layer hydrogel is a PAM-PEA hydrogel. The adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

[0066] The above-mentioned strong wet adhesion material was applied to the rapid repair of cracks in underwater suspended tunnels. The specific method and application process are the same as those in the comparative example.

[0067] The swelling rate and wet adhesion strength of the strong wet adhesion material in this embodiment were tested.

[0068] Test results are as follows Figure 4 , Figure 5 As shown in the figure, the test results of this embodiment correspond to A4 in the figure.

[0069] Example 3 This embodiment provides a method for preparing a strong wet adhesion material. In this embodiment, the mass ratio of dopamine (DA) to acrylamide (AM) in step 2) is DA : AM = 6 wt% (A6).

[0070] The remaining steps are the same as in the comparative example.

[0071] The strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel. The components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction. The tough layer hydrogel is a PAM-PEA hydrogel. The adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

[0072] The above-mentioned strong wet adhesion material was applied to the rapid repair of cracks in underwater suspended tunnels. The specific method and application process are the same as those in the comparative example.

[0073] The swelling rate and wet adhesion strength of the strong wet adhesion material in this embodiment were tested.

[0074] Test results are as follows Figure 4 , Figure 5 As shown in the figure, the test results of this embodiment correspond to A6 in the figure.

[0075] Example 4 This embodiment provides a method for preparing a strong wet adhesion material. In this embodiment, the mass ratio of dopamine (DA) to acrylamide (AM) in step 2) is DA : AM = 8 wt% (A8).

[0076] The remaining steps are the same as in the comparative example.

[0077] The strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel. The components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction. The tough layer hydrogel is a PAM-PEA hydrogel. The adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

[0078] The above-mentioned strong wet adhesion material was applied to the rapid repair of cracks in underwater suspended tunnels. The specific method and application process are the same as those in the comparative example.

[0079] The swelling rate and wet adhesion strength of the strong wet adhesion material in this embodiment were tested.

[0080] Test results are as follows Figure 4 , Figure 5 As shown in the figure, the test results of this embodiment correspond to A8 in the figure.

[0081] contrast Figure 4 , Figure 5The test results of the comparative examples and Examples 1-4 show that with the increase of dopamine (DA) content, the equilibrium swelling ratio (SR), wet adhesion strength, and adhesion energy also tend to increase. When the mass ratio of dopamine (DA) to acrylamide (AM) is 8 wt% (A8), the strong wet adhesion material has the highest wet adhesion strength of 136.5 kPa and the highest adhesion energy of approximately 48 J / m. 2 Although the equilibrium swelling rate at this time is slightly higher than that without DA (0 wt%) (A0), it is still only 38.21%, indicating that the strong wet adhesion material provided in Example 4 has good anti-swelling and wet adhesion properties, and has good application prospects as a strong wet adhesion material for rapid repair of cracks in underwater suspended tunnels.

[0082] Example 5 This embodiment provides a method for preparing a strong wet adhesion material, including the following steps: 1) Acrylamide (AM), ethyl 2-phenoxyacrylate (PEA), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were added to a dimethyl sulfoxide (DMSO) solution in a reaction mold. The total concentration of acrylamide (AM) and ethyl 2-phenoxyacrylate (PEA) was 5 mol / L, with ethyl 2-phenoxyacrylate (PEA) accounting for 90% of the total concentration. The concentration of N,N'-methylenebisacrylamide (MBAA) was 2.5 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 The solution was stirred evenly with a magnetic stirrer, then degassed by ultrasound, and then reacted by water bath heating to obtain PAM-PEA hydrogel, i.e., tough layer hydrogel. The stirring rate was 300 rpm, the stirring time was 10 min, the ultrasound power was 200 W, the ultrasound time was 15 min, the water bath heating temperature was 60℃, and the water bath heating time was 0.5 h.

[0083] 2) Dopamine (DA) was dissolved in deionized water, and clay nanosheets (Clay) were added. The mixture was stirred for 5 hours at a stirring rate of 550 rpm to allow dopamine intercalation and oxidation, preparing a clay-polydopamine (clay-PDA) suspension. Acrylamide (AM), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were then added to this clay-polydopamine suspension to obtain a reaction solution. The concentration of acrylamide (AM) was 5 mol / L, the mass ratio of dopamine (DA) to acrylamide (AM) was DA : AM = 8 wt%, the mass ratio of clay nanosheets (Clay) to acrylamide (AM) was Clay : AM = 12 wt%, and the concentration of N,N'-methylenebisacrylamide (MBAA) was 2.5 × 10⁻⁶.-4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. - 3 After stirring evenly with mol / L, the solution was degassed by ultrasound. The reaction solution was then poured onto the upper surface of the tough hydrogel obtained in step 1). PDA-clay-PAM hydrogel, i.e., the adhesion layer hydrogel, was prepared by water bath heating, thus obtaining a double-layer hydrogel. This double-layer hydrogel is a strong wet adhesion material. The stirring rate was 550 rpm, the stirring time was 25 min, the ultrasound power was 200 W, the ultrasound time was 30 min, the water bath heating temperature was 80℃, and the water bath heating time was 1 h.

[0084] Figure 1 This is a schematic diagram of the tough-adhesive bilayer structure of the strong wet adhesion material provided by the present invention, as shown below. Figure 1 As shown, the strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel; the components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction; the tough layer hydrogel is PAM-PEA hydrogel; the adhesion layer hydrogel is PDA-clay-PAM hydrogel.

[0085] The aforementioned strong moisture-adhesive material was applied to the rapid repair of cracks in underwater suspended tunnels. Specifically, the material was directly adhered to the surface of a cracked concrete specimen immersed in water, as illustrated in the diagram. Figure 2 As shown. The application process includes the following steps: S1) Prepare a tubular concrete specimen model with cracks to simulate the shape of an underwater suspended tunnel. The specimen is 4 cm thick, 50 cm high, 30 cm in outer diameter, and the crack width is 0.2 mm. S2) Fix the lower end of the tubular concrete specimen model to the bottom of the water tank with epoxy resin, fill the water tank with water to a level higher than the crack, so that the crack becomes the only water inlet point, cut the prepared strong wet adhesion material to the corresponding size, and stick it to the crack. The pH of the aqueous solution is 9.0 to simulate a slightly alkaline water environment.

[0086] Example 6 This embodiment provides a method for preparing a strong wet adhesion material, including the following steps: 1) Acrylamide (AM), ethyl 2-phenoxyacrylate (PEA), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) are added to a dimethyl sulfoxide (DMSO) solution in a reaction mold. The total concentration of acrylamide (AM) and ethyl 2-phenoxyacrylate (PEA) is 2 mol / L, the concentration of ethyl 2-phenoxyacrylate (PEA) is 70% of the total concentration, and the concentration of N,N'-methylenebisacrylamide (MBAA) is 1 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 The solution was stirred evenly with a magnetic stirrer, then degassed by ultrasound, and then reacted by water bath heating to obtain PAM-PEA hydrogel, i.e., tough layer hydrogel. The stirring rate was 300 rpm, the stirring time was 10 min, the ultrasound power was 200 W, the ultrasound time was 15 min, the water bath heating temperature was 60℃, and the water bath heating time was 0.5 h.

[0087] 2) Dopamine (DA) was dissolved in deionized water, and clay nanosheets (Clay) were added. The mixture was stirred for 5 hours at a stirring rate of 550 rpm to allow dopamine intercalation and oxidation, preparing a clay-polydopamine (clay-PDA) suspension. Acrylamide (AM), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were then added to this clay-polydopamine suspension to obtain a reaction solution. The concentration of acrylamide (AM) was 2 mol / L, the mass ratio of dopamine (DA) to acrylamide (AM) was DA : AM = 4 wt%, the mass ratio of clay nanosheets (Clay) to acrylamide (AM) was Clay : AM = 4 wt%, and the concentration of N,N'-methylenebisacrylamide (MBAA) was 1 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 After stirring evenly with mol / L, the solution was degassed by ultrasound. The reaction solution was then poured onto the upper surface of the tough hydrogel obtained in step 1). PDA-clay-PAM hydrogel, i.e., the adhesion layer hydrogel, was prepared by water bath heating, thus obtaining a double-layer hydrogel. This double-layer hydrogel is a strong wet adhesion material. The stirring rate was 550 rpm, the stirring time was 25 min, the ultrasound power was 200 W, the ultrasound time was 30 min, the water bath heating temperature was 80℃, and the water bath heating time was 1 h.

[0088] Figure 1 This is a schematic diagram of the tough-adhesive bilayer structure of the strong wet adhesion material provided by the present invention, as shown below. Figure 1As shown, the strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel; the components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction; the tough layer hydrogel is PAM-PEA hydrogel; the adhesion layer hydrogel is PDA-clay-PAM hydrogel.

[0089] The aforementioned strong moisture-adhesive material was applied to the rapid repair of cracks in underwater suspended tunnels. Specifically, the material was directly adhered to the surface of a cracked concrete specimen immersed in water, as illustrated in the diagram. Figure 2 As shown. The application process includes the following steps: S1) Prepare a tubular concrete specimen model with cracks to simulate the shape of an underwater suspended tunnel. The specimen is 4 cm thick, 50 cm high, 30 cm in outer diameter, and the crack width is 0.2 mm. S2) Fix the lower end of the tubular concrete specimen model to the bottom of the water tank with epoxy resin, fill the water tank with water to a level higher than the crack, so that the crack becomes the only water inlet point, cut the prepared strong wet adhesion material to the corresponding size, and stick it to the crack. The pH of the aqueous solution is 6.0 to simulate a slightly acidic water environment.

[0090] Example 7 This embodiment provides a method for preparing a strong wet adhesion material, including the following steps: 1) Acrylamide (AM), ethyl 2-phenoxyacrylate (PEA), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were added to a dimethyl sulfoxide (DMSO) solution in a reaction mold. The total concentration of acrylamide (AM) and ethyl 2-phenoxyacrylate (PEA) was 3 mol / L, with ethyl 2-phenoxyacrylate (PEA) accounting for 80% of the total concentration. The concentration of N,N'-methylenebisacrylamide (MBAA) was 1.5 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 The solution was stirred evenly with a magnetic stirrer, then degassed by ultrasound, and then reacted by water bath heating to obtain PAM-PEA hydrogel, i.e., tough layer hydrogel. The stirring rate was 300 rpm, the stirring time was 10 min, the ultrasound power was 200 W, the ultrasound time was 15 min, the water bath heating temperature was 60℃, and the water bath heating time was 0.5 h.

[0091] 2) Dopamine (DA) was dissolved in deionized water, and clay nanosheets (Clay) were added. The mixture was stirred for 5 hours at a stirring rate of 550 rpm to allow dopamine intercalation and oxidation, preparing a clay-polydopamine (clay-PDA) suspension. Acrylamide (AM), N,N'-methylenebisacrylamide (MBAA), and potassium persulfate (KPS) were then added to this clay-polydopamine suspension to obtain a reaction solution. The concentration of acrylamide (AM) was 3 mol / L, the mass ratio of dopamine (DA) to acrylamide (AM) was DA : AM = 6 wt%, the mass ratio of clay nanosheets (Clay) to acrylamide (AM) was Clay : AM = 8 wt%, and the concentration of N,N'-methylenebisacrylamide (MBAA) was 1.5 × 10⁻⁶. -4 The concentration of potassium persulfate (KPS) is 0.5 × 10 mol / L. -3 After stirring evenly with mol / L, the solution was degassed by ultrasound. The reaction solution was then poured onto the upper surface of the tough hydrogel obtained in step 1). PDA-clay-PAM hydrogel, i.e., the adhesion layer hydrogel, was prepared by water bath heating, thus obtaining a double-layer hydrogel. This double-layer hydrogel is a strong wet adhesion material. The stirring rate was 550 rpm, the stirring time was 25 min, the ultrasound power was 200 W, the ultrasound time was 30 min, the water bath heating temperature was 80℃, and the water bath heating time was 1 h.

[0092] Figure 1 This is a schematic diagram of the tough-adhesive bilayer structure of the strong wet adhesion material provided by the present invention, as shown below. Figure 1 As shown, the strong wet adhesion material prepared by the above preparation method is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesion layer hydrogel; the components of the adhesion layer hydrogel penetrate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction; the tough layer hydrogel is PAM-PEA hydrogel; the adhesion layer hydrogel is PDA-clay-PAM hydrogel.

[0093] The aforementioned strong moisture-adhesive material was applied to the rapid repair of cracks in underwater suspended tunnels. Specifically, the material was directly adhered to the surface of a cracked concrete specimen immersed in water, as illustrated in the diagram. Figure 2 As shown. The application process includes the following steps: S1) Prepare a tubular concrete specimen model with cracks to simulate the shape of an underwater suspended tunnel. The specimen is 4 cm thick, 50 cm high, 30 cm in outer diameter, and the crack width is 0.2 mm. S2) Fix the lower end of the tubular concrete specimen model to the bottom of the water tank with epoxy resin, fill the water tank with water to a level higher than the crack, so that the crack becomes the only water inlet point, cut the prepared strong wet adhesion material to the corresponding size, and stick it to the crack. The pH of the aqueous solution is 7.0 to simulate a neutral water environment.

[0094] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. An application of a strong moisture-adhesive material, characterized in that, The strong wet adhesion material was used for rapid repair of cracks in underwater suspended tunnels. The preparation method of the strong wet adhesion material includes the following steps: 1) Add acrylamide, ethyl 2-phenoxyacrylate, dimethyl sulfoxide, the first crosslinking agent and the first initiator to the reaction mold, stir evenly, sonicate, and heat to obtain PAM-PEA hydrogel, i.e. tough layer hydrogel. 2) Prepare a clay-polydopamine suspension by mixing dopamine, water, and clay nanosheets. Add acrylamide, a second crosslinking agent, and a second initiator to the clay-polydopamine suspension. Stir and sonicate to obtain a reaction solution. Pour the obtained reaction solution onto the upper surface of the tough hydrogel obtained in step 1). Heat the solution to synthesize a PDA-clay-PAM hydrogel, which is the adhesion layer hydrogel, thus obtaining a double-layer hydrogel, which is the strong wet adhesion material.

2. The application of the strong wet adhesion material according to claim 1, characterized in that, In step 1), the first crosslinking agent is N,N'-methylenebisacrylamide; The first initiator is potassium persulfate.

3. The application of the strong wet adhesion material according to claim 1, characterized in that, In step 1), the total concentration of acrylamide and ethyl 2-phenoxyacrylate is 2-5 mol / L, wherein the molar ratio of ethyl 2-phenoxyacrylate is 70-90%. The concentration of the first crosslinking agent is 1×10⁻⁶. -4 -2.5×10 -4 mol / L; The concentration of the first initiator is 0.2 × 10⁻⁶. -3 -0.8×10 -3 mol / L.

4. The application of the strong wet adhesion material according to claim 1, characterized in that, The stirring rate described in step 1) is 300 rpm, and the time is 5-15 min; The ultrasound power in step 1) is 200 W, and the duration is 10-20 min; The heating described in step 1) is water bath heating, with a heating temperature of 55-65℃ and a heating time of 20-40 min.

5. The application of the strong wet adhesion material according to claim 1, characterized in that, In step 2), the second crosslinking agent is N,N'-methylenebisacrylamide; The second initiator is potassium persulfate.

6. The application of the strong wet adhesion material according to claim 1, characterized in that, The concentration of acrylamide mentioned in step 2) is 2-5 mol / L; In step 2), the mass ratio of dopamine to acrylamide is DA:AM = x%, where 0 < x ≤ 8. In step 2), the mass ratio of clay nanosheets to acrylamide is Clay:AM = 4-12%. The concentration of the second crosslinking agent is 1×10 -4 -2.5×10 -4 mol / L; The concentration of the second initiator is 0.2 × 10⁻⁶. -3 -0.8×10 -3 mol / L.

7. The application of the strong wet adhesion material according to claim 1, characterized in that, The stirring speed described in step 2) is 550 rpm, and the time is 20-30 min; The ultrasound power in step 2) is 200 W, and the duration is 20-40 min; The heating described in step 2) is water bath heating, with a temperature of 75-85℃ and a time of 50-70 min.

8. The application of the strong wet adhesion material according to claim 1, characterized in that, The preparation of the clay-polydopamine suspension in step 2) specifically includes the following steps: Dopamine was dissolved in water to obtain a DA aqueous solution; clay nanosheets were added to the obtained DA aqueous solution to prepare a clay-DA suspension; the obtained clay-DA suspension was stirred at 550 rpm for 5 h to obtain a clay-polydopamine suspension.

9. The application of the strong wet adhesion material according to claim 1, characterized in that, The strong wet adhesion material is a bilayer hydrogel, which includes a tough layer hydrogel and an adhesive layer hydrogel. The components of the adhesive layer hydrogel permeate into the network of the tough layer hydrogel, and there is an interlocking structure at the junction; The tough layer hydrogel is a PAM-PEA hydrogel. The adhesion layer hydrogel is a PDA-clay-PAM hydrogel.

Citation Information

Patent Citations

  • Solvent-free elastic epoxy grouting material and preparation method and application thereof

    CN102775737A

  • Preparation method of conductive double-layer hydrogel for integral regeneration of bone and cartilage by electrical stimulation

    CN110128679A